Life Cycle Assessment of Sustainable Building Materials in the Nigerian Construction Industry - Unegbu, H C O; Yawas, Danjuma Saleh (Fakultas Teknik Universitas Brawijaya, 2025)
This study presented a comprehensive life cycle assessment (LCA) of sustainable building materials within the Nigerian construction industry, focusing on bamboo, recycled steel, and low-carbon concrete. The research aimed to evaluate the environmental impacts of these materials across all stages of their life cycles, from raw material extraction to end-of-life disposal. A mixed-methods approach was employed, with primary data gathered through interviews and surveys with industry professionals, while secondary data was obtained from reputable databases and literature. The results indicated that bamboo was the most environmentally friendly material, exhibiting the lowest global warming potential, ozone depletion, eutrophication, and resource depletion impacts. Low-carbon concrete also demonstrated significant environmental benefits, particularly in reducing greenhouse gas emissions compared to conventional concrete. Recycled steel, while advantageous in promoting the circular economy, incurred higher energy consumption and emissions due to the energy-intensive recycling process. The study identified several barriers to the widespread adoption of sustainable materials in Nigeria, including high initial costs, limited availability, and a lack of regulatory support. To address these challenges, the research suggested strengthening regulatory frameworks, providing financial incentives, enhancing local production capabilities, and increasing awareness through education and training programs. The findings underscored the potential of sustainable materials to reduce the environmental footprint of construction activities in Nigeria, highlighting the need for coordinated efforts to promote their adoption. This study contributed valuable insights to policymakers, industry stakeholders, and researchers focused on advancing sustainability in the built environment.